Clinical utility of square-wave jerks in neurology and psychiatry - Zachou, Athena; Armenis, Georgios; Stamelos, Ioannis; Stratigakou-Polychronaki, Eirini; Athanasopoulos, Fotios; Anagnostou, Evangelos (Frontiers in Ophthalmology, 2024)
Human eye fixation is steadily interrupted by small, physiological or abnormal, eye movements. Square-wave jerks (SWJ) are the most common saccadic intrusion which can be readily seen at the bedside and also quantified using oculographic techniques.Various neurological, neuropsychiatric and psychiatric disorders display abnormal fixational eye movement patterns characterized by frequent SWJ. For the clinician, SWJ are particularly important because they can be readily observed at the bedside.Here, we will discuss the pathological conditions that present with SWJ and explore the expanding body of literature suggesting that SWJ may serve as a potential indicator for various clinical conditions.